Analisis Pengaruh Marketing Mix 4P terhadap Kepuasan Konsumen Ayam Frozen Prima Freshmart di Kabupaten Kendal - Rahma, Tasya Mifdatul; Budiraharjo, Kustopo; Setiadi, Agus (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The increasing level of chicken meat consumption in Kendal Regency has caused competition for the sale of chicken meat which also increase. Chicken meat is not only sold in traditional markets but is now starting to spread to modern markets where it is sold in frozen. Companies need to develop their marketing to be able to compete by increasing consumer satisfaction, one of which is through the marketing mix 4p. Consumer satisfaction is an emotional assessment where consumer expectations and needs are met. This research aims to determine the application of the marketing mix 4p and the influence of the marketing mix 4p on consumer satisfaction of Prima Freshmart frozen chicken in Kendal Regency. This research was conducted at Prima Freshmart in 3 sub-districts in Kendal Regency, namely Boja, Kaliwungu and Pegandon in November - December 2023. The research method used was a survey method using questionnaires. Sampling used the accidental sampling method with a total of 120 respondents. Data analysis used descriptive analysis and multiple linear regression analysis. The research results show that the implementation of the 4p marketing mix carried out by Prima Freshmart has been implemented well. Product, price, place and promotion simultaneously and partially influence consumer satisfaction for Prima Freshmart frozen chicken in Kendal Regency. The coefficient of determination is 0.789, which means that  product price, place and promotion explain the consumer satisfaction value of Prima Freshmart frozen chicken in Kendal Regency by 78.9% and the remaining 21.1% is explained by other variables not studied.